ХАРАКТЕРИСТИКА СРЕДСТВ И МЕТОДОВ РАЗВИТИЯ ОБЩЕЙ И СПЕЦИАЛЬНОЙ ФИЗИЧЕСКОЙ ПОДГОТОВКИ БАСКЕТБОЛИСТОВ - Авезбаев, А.Х. (SCIENCE and SOCIETY, 2022)
This article discusses and substantiates the methodology for improving the technical training of young basketball players, the essence of which is to intensify the process of performing the learned techniques and gradually bringing the conditions for their implementation to the game ones. The data obtained will contribute to the most effective correction of the training process of basketball players, which will further improve the effectiveness of the competitive activity of basketball players.